2013
DOI: 10.2139/ssrn.2326429
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Connectedness Predict Crises?

Abstract: The global financial crisis has reignited interest in models of crisis prediction. It has also raised the question whether financial connectedness-a possible source of systemic riskcan serve as an early warning indicator of crises. In this paper we examine the ability of connectedness in the global network of financial linkages to predict systemic banking crises. Our results indicate that increases in a country's financial interconnectedness and decreases in its neighbors' connectedness are associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…The clustering coefficient (here defined as in Barrat et al 2004) measures the strength of connections among the neighbors of a country (loosely speaking, the degree of "friendship" among a country's "friends"). In the years 2000-2004, the clustering coefficient increased noticeably, consistent with similar findings by Minoiu et al (2013). From 2004-06, clustering in the sovereign bond yield network was high, with the average clustering coefficient around 97 percent ( Figure 5).…”
Section: Within Europesupporting
confidence: 85%
See 1 more Smart Citation
“…The clustering coefficient (here defined as in Barrat et al 2004) measures the strength of connections among the neighbors of a country (loosely speaking, the degree of "friendship" among a country's "friends"). In the years 2000-2004, the clustering coefficient increased noticeably, consistent with similar findings by Minoiu et al (2013). From 2004-06, clustering in the sovereign bond yield network was high, with the average clustering coefficient around 97 percent ( Figure 5).…”
Section: Within Europesupporting
confidence: 85%
“…Several authors have shown network measures to be significant correlates of banking system and general financial system stress. Minoiu et al (2013) found rising interconnectedness (measured as clustering coefficients and degree centrality) in the global network of cross-border banking exposures from the BIS locational statistics to be significant predictors of systemic banking crises. So were degree and betweenness centrality in a bank-level network of syndicated loans (Caballero, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Thus researchers are forced to look for suitable proxies which are widely available and sufficiently reflect network dependencies. For instance, Minoiu, Kang, Subrahmanian, and Berea (2013) quantify the connectivity between banks based on BIS bilateral locational statistics representing stocks of cross-border assets held by banking systems. Alter, Craig, and Raupach (2015) utilize a dataset of credit exposures of the German banking system.…”
mentioning
confidence: 99%
“…This would improve our ability to forecast financial markets and economic developments in general, and be useful for risk management purposes. For example, Minoiu et al (2014) use network analysis to find that financial connectedness can be useful in predicting banking crises 1 . Using connectedness measures as an early warning indicator of crisis is of course an important application of system-wide connectedness.…”
Section: Financial Market Wide Dependencesmentioning
confidence: 99%